Net Zero Energy for Industrial and Commercial Microgrids: Approaches and Challenges - Bandeiras, Filipe (2021)
This paper addresses the concept of net zero energy and net metering in efficient buildings in order to assist in the study and development of future microgrids for buildings with annual zero energy consumption. There are several definitions for zero energy buildings available in the literature with a distinct set of project goals and interests, but this work is focused on the definition that accounts for energy losses by converting each energy type to source energy. Finally, a case study is presented to evaluate whether four distinct all-electric buildings can achieve annual zero energy by deploying on-site renewable sources within their site boundary.